Lead and Cadmium Levels and Balance and Vestibular Dysfunction among Adult Participants in the National Health and Nutrition Examination Survey (NHANES) 1999–2004 - Min, Kyoung-Bok (National Institute of Environmental Health Sciences, 2012)
Background: Few studies have been conducted to identify risk factors for balance and vestibular dysfunction in general populations, but previous studies have reported evidence of adverse effects of lead and cadmium on balance control in high-risk groups. Objective: We evaluated the relationship between blood lead and cadmium levels and balance and vestibular dysfunction in a general population study. Methods: We analyzed data from the 1999–2004 National Health and Nutrition Examination Survey (NHANES) of 5,574 adults ≥ 40 years of age. Balance dysfunction was evaluated by the Romberg Test of Standing Balance on Firm and Compliant Support Surfaces, which examines the ability to stand unassisted using four test conditions to evaluate vestibular system, vision, and proprioception inputs that contribute to balance. Blood levels of lead and cadmium were measured by atomic absorption spectrometry. Associations were estimated using logistic regression models adjusted for potential confounders. Associations with time to loss of balance were estimated using adjusted Cox proportional hazard models. Results: The adjusted odds ratio (OR) for balance dysfunction in association with the highest quintile (3.3–48 µg/dL) versus the lowest quintile (< 1.2 µg/dL) of lead was 1.42 [95% confidence interval (CI): 1.07, 1.89]. The corresponding OR for cadmium (0.9–7.4 µg/L vs. < 0.2 µg/L) was 1.27 (95% CI: 1.01, 1.60). The adjusted hazard ratio for time to failure for the most physiologically challenging balance test among subjects with the highest vs. lowest quintiles of blood lead was 1.24 (95% CI: 1.04, 1.48). Cadmium levels were not associated with time to failure. Conclusions: Our findings suggest that blood lead and cadmium levels may be associated with balance and vestibular dysfunction in a general sample of U.S. adults.